Rod-like transition first or chain aggregation first? ordered aggregation of rod-like poly(p-phenyleneethynylene) chains in solution. Issue 89 (18th October 2019) - Hattori, Yusuke; Nishimura, Nozomi; Tsutsui, Yusuke; Ghosh, Samrat; Sakurai, Tsuneaki; Sugiyasu, Kazunori; Takeuchi, Masayuki; Seki, Shu
Abstract : Extremely small energetic disorder of electronically-conjugated poly( p -phenyleneethynylene) chains. Abstract : The rod-like configuration of conjugated polymer chains with its low energetic disorder is the key to utilizing the backbone as a highly electrically-conductive wire. An energetic disorder that is higher than 0.1 eV, coupled with vibronic modes of the chains, leads to the localization of charges. Herein, we have tracked precisely the rod-like transition of poly( p -phenyleneethynylene) (PPE) chains as a function of temperature in diluted solutions, and shown a steep increase in persistence length at 230 K. The resulting rod-like configuration of the PPE chains with its extended electronic conjugation exhibited an extremely small energetic disorder of ∼70 meV, and was stabilized by subsequent polymer aggregate formation.